A multisite evaluation of summer camps for children with cancer and their siblings. Issue 6 (1st November 2016) - Wu, Yelena P.; McPhail, Jessica; Mooney, Ryan; Martiniuk, Alexandra; Amylon, Michael D.
ABSTRACT: Summer camps for pediatric cancer patients and their families are ubiquitous. However, there is relatively little research, particularly studies including more than one camp, documenting outcomes associated with children's participation in summer camp. The current cross-sectional study used a standardized measure to examine the role of demographic, illness, and camp factors in predicting children's oncology camp-related outcomes. In total, 2, 114 children at 19 camps participated. Campers were asked to complete the pediatric camp outcome measure, which assesses camp-specific self-esteem, emotional, physical, and social functioning. Campers reported high levels of emotional, physical, social, and self-esteem functioning. There were differences in functioning based on demographic and illness characteristics, including gender, whether campers/siblings were on or off active cancer treatment, age, and number of prior years attending camp. Results indicated that summer camps can be beneficial for pediatric oncology patients and their siblings, regardless of demographic factors (e.g., gender, treatment status) and camp factors (e.g., whether camp sessions included patients only, siblings only, or both). Future work could advance the oncology summer camp literature by examining other outcomes linked to summer camp attendance, using longitudinal designs, and including comparison groups.